2018
DOI: 10.1186/s40945-018-0046-z
|View full text |Cite
|
Sign up to set email alerts
|

Rasch analysis of the patient-rated wrist evaluation questionnaire

Abstract: BackgroundThe Patient-Rated Wrist Evaluation (PRWE) was developed as a wrist joint specific measure of pain and disability and evidence of sound validity has been accumulated through classical psychometric methods. Rasch analysis (RA) has been endorsed as a newer method for analyzing the clinical measurement properties of self-report outcome measures. The purpose of this study was to evaluate the PRWE using Rasch modeling.MethodsWe employed the Rasch model to assess overall fit, response scaling, individual it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 31 publications
0
17
0
1
Order By: Relevance
“…Although reliability indices should be compared with caution across potentially different study conditions, it is noteworthy that the PSI obtained for the ABILHAND-HS (0.90) was higher than prior values obtained for the activities subscales of the PRWE [ 52 ] (0.78 and 0.81 for the usual and specific activities subscales, respectively, in DRF patients), for the Patient-Rated Wrist and Hand Evaluation [ 53 ] (0.83 in HS patients), for the QuickDASH scale [ 54 ] (0.84 in patients with various upper limb dysfunctions) and for the Manual Ability Measure [ 55 ] (MAM-16; 0.83 for HS patients), while being equal to that for the DASH manual functioning subscale [ 18 ]. PSI values reflect sensitivity to clinical evolution over time, with greater values indicating a greater number of distinguishable ability strata.…”
Section: Discussionmentioning
confidence: 99%
“…Although reliability indices should be compared with caution across potentially different study conditions, it is noteworthy that the PSI obtained for the ABILHAND-HS (0.90) was higher than prior values obtained for the activities subscales of the PRWE [ 52 ] (0.78 and 0.81 for the usual and specific activities subscales, respectively, in DRF patients), for the Patient-Rated Wrist and Hand Evaluation [ 53 ] (0.83 in HS patients), for the QuickDASH scale [ 54 ] (0.84 in patients with various upper limb dysfunctions) and for the Manual Ability Measure [ 55 ] (MAM-16; 0.83 for HS patients), while being equal to that for the DASH manual functioning subscale [ 18 ]. PSI values reflect sensitivity to clinical evolution over time, with greater values indicating a greater number of distinguishable ability strata.…”
Section: Discussionmentioning
confidence: 99%
“… 11 The second was conducted on a distal radius fracture population using the PRWE version. 5 Concordance in Rasch findings between the PRWHE and PRWE can support the assumption that these measures can be used interchangeably. Rasch analysis can complement the findings obtained from FA, because it provides some overlapping information (ie, factor structure, unidimensionality) and some distinct measurement indicators such DIF and targeting.…”
mentioning
confidence: 90%
“… 10 Two studies have previously reported the clinical measurement properties of the PRWHE and PRWE using Rasch analysis. 5 , 11 They found no significant differential item functioning (DIF) or scale differences between individuals with injuries in the dominant hand when compared with injuries in the nondominant hand. They reported that 2 subscales (pain and function) were well targeted and had high reliability.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Rasch model is widely applied to evaluate psychological measurement tools such as personality disorders [7], patientrated wrist evaluation [8], Hospital Anxiety and Depression Scale (HADS) [9], Depression Anxiety and Stress Scale [10], and bullying [11] and so on. Besides the Rasch model is also used to evaluate examination questions in mathematics course [12].…”
Section: Introductionmentioning
confidence: 99%